Cluster of Neisseria gonorrhoeae Isolates With High-level Azithromycin Resistance and Decreased Ceftriaxone Susceptibility, Hawaii, 2016 - Katz, Alan R. (Clin Infect Dis, 2017)
BACKGROUND: The Centers for Disease Control and Prevention (CDC) currently recommends dual therapy with ceftriaxone and azithromycin for gonorrhea to ensure effective treatment and slow emergence of antimicrobial resistance. Since 2013, the prevalence of reduced azithromycin susceptibility increased in the United States; however, these strains were highly susceptible to cephalosporins. We identified a cluster of Neisseria gonorrhoeae isolates with high-level azithromycin resistance, several of which also demonstrated decreased ceftriaxone susceptibility. METHODS: Eight N. gonorrhoeae isolates collected from 7 patients on Oahu, Hawaii, seen 21 April 2016 through 10 May 2016 underwent routine Etest antimicrobial susceptibility testing by the Hawaii Department of Health. All demonstrated elevated azithromycin minimum inhibitory concentrations (MICs) >256 μg/mL and elevated ceftriaxone MICs (≥0.125 μg/mL). Isolates were sent to the University of Washington and CDC for confirmatory agar dilution testing; sequence data were sent to CDC for analysis. All patients were interviewed and treated, and when possible, partners were interviewed, tested, and treated. RESULTS: All isolates had azithromycin MICs >16 μg/mL and 5 had ceftriaxone MICs = 0.125 μg/mL by agar dilution. All isolates were β-lactamase positive and were resistant to penicillin, tetracycline, and ciprofloxacin. Genomic analysis revealed genetic relatedness. No patients reported recent travel or antibiotic use, and no male patients reported male sex partners. All patients were successfully treated. CONCLUSIONS: This cluster of genetically related gonococcal isolates with decreased ceftriaxone susceptibility and high-level azithromycin resistance may bring the threat of treatment failure in the United States with the current recommended dual therapy one step closer.